The effectiveness of cognitive behavioural therapy for patients with concurrent hand and psychological disorders. (January 2023) - Lucas, Vicky J.; Burke, Sarah; Selby, Anna; Johnson, Nick A.
We investigated the effectiveness of cognitive behavioural therapy (CBT) for patients with psychological disorders thought to be influencing recovery from elective and traumatic hand conditions. Demographic data and psychological assessment scores (Primary Health Questionnaire 9 (PHQ9), General Anxiety Disorder Assessment (GAD7), Impact of Event Scale (IES)) were prospectively collected before and after CBT treatment. One hundred and fourteen patients underwent CBT with 81 completing treatment. Full data was available for 78 (68%) patients. Mean age was 43 (range 13–84) and 63% were women. Sixty-one per cent had sustained a traumatic hand injury. PHQ9, GAD7 and IES scores decreased significantly following treatment. Many patients with hand conditions have associated psychological problems that may influence outcome. CBT in a hand unit setting appears to be an effective treatment. Further research with a control group should investigate whether CBT improves psychological health or if this may occur as patients recover from their physical hand disorder regardless of CBT. Level of evidence: IV